Non-collinear magnetism of Cr nanostructures on Fe-3ML/Cu(001): First principles and experimental investigations - Lounis, S.; Reif, M.; P. Mavropoulos; Glaser, L.; P.H. Dederichs; Martins, M.; S. Blügel; Wurth, W. (EPL, 2008)
A combined experimental, using the X-ray magnetic circular dichroism, and theoretical investigation, using the full-potential Korringa-Kohn-Rostoker (KKR) Green function method, is carried out to study the spin structure of small magnetic Cr adatom clusters on the surface of 3 monolayers of fcc Fe deposited on Cu(001). The exchange interaction between the different Cr adatoms as well as between the Cr atoms and the Fe atoms is of antiferromagnetic nature and of comparable magnitude, leading due to frustration to complex non-collinear magnetic configurations. The presence of non-collinear magnetic coupling obtained by ab initio calculations is confirmed by the experimental results. Copyright (C) EPLA, 2008.